Desain Sistem Pembangkit Listrik Tenaga Surya Off-Grid untuk Catu Daya Sistem Refrigerasi - Andriyanto Setyawan; Tandi Sutandi; Markus Markus (Retii, 2018)
This paper discusses the use of solar energy that is easily found in Indonesia due to its geographical location in tropical area. In this research, the solar energy was utilized to supply energy for the operation of refrigeration machine that highly required in Indonesia. This research employed solar panels with a capacity of 200 WP, solar charge controller, battery, and inverter, to supply energy for a mini refrigerator. The average power resulted from the experiment is 106.4 Watt with the average solar irradiation of 352 W/m2. The energy for the charging of the battery is 396 Wh. This is sufficient for supplying the refrigerating machine for 3.3 hours if the machine runs continuously. If the machine has an on/off cycle with the utilization factor of 40%, the energy could run the machine for 8.25 hours.